Clozapine-Induced Microseizures, Orofacial Dyskinesia, and Speech Dysfluency in an Adolescent with Treatment Resistant Early Onset Schizophrenia on Concurrent Lithium Therapy - Vivekananda Rachamallu; Ayman Haq; Michael M. Song; Manish Aligeti (Case Reports in Psychiatry)
Clozapine is an atypical antipsychotic used in the treatment of refractory schizophrenia. It has a well-known side effect profile, including agranulocytosis, decreased seizure threshold, and tardive dyskinesia. In addition, numerous case reports have described clozapine-induced stuttering in adults. However, there has been only one previous case report describing it in the adolescent population. In addition, concurrent lithium therapy has been shown to enhance the neurotoxic effects of antipsychotics and lower the seizure threshold. Here, we report on the development of clozapine-induced microseizures, orofacial dyskinesia, and stuttering in a 17-year-old adolescent male with treatment of refractory early onset schizophrenia on clozapine and concurrent lithium therapy. The patient’s symptoms of schizophrenia responded well to the clozapine regimen. However, with the escalating dose of clozapine, the patient developed speech dysfluency in the form of stuttering and perioral twitching. An electroencephalogram confirmed seizure activity. Due to similarities with tardive dyskinesia, symptoms of microseizures induced by atypical antipsychotics may not be accurately diagnosed. A multidisciplinary treatment of speech dysfluency is of particular importance in the adolescent schizophrenic patients, who are expected to have longer duration of lifetime exposure to antipsychotics and in whom peer group interaction is crucial for normal personal and social development.